Parametrization for chemical freeze-out conditions from net-charge fluctuations measured at RHIC. (April 2015) - Bluhm, M; Alba, P; Alberico, W; Bellwied, R; Sarti, V Mantovani; Nahrgang, M; Ratti, C
Abstract: We discuss details of our thermal model applied to extract chemical freeze-out conditions from fluctuations in the net-electric charge and net-proton number measured at RHIC. A parametrization for these conditions as a function of the beam energy is given.